Features of obtaining and properties of thin films organic semiconductors = Особливості отримання і властивостей тонких плівок органічних напівпровідників : ст. - Tsizh, B.; Dziamski, Z. (Stepan Gzhytskyi National University of Veterinary Medicine and Biotechnologies ; Kazimierz Wielki University in Bydgoszcz, 2023)
In recent decades, thin films of organic semiconductors (OS), or, as they are also called, organic molecular crystals, have attracted special attention in connection with a number of proposals for their use in functional units of modern electronics, and therefore in modern technological equipment. At the same time, the optical, electrophysical and photoelectric properties of OS are very important, which are determined both by the structure of organic molecules, that is, the starting material, and by the crystal structure of condensates, that is, by the technological conditions of film production. In this regard, this article presents the results of studies of some properties of OS and the technology of obtaining thin films based on them. OS are characterized by weak intermolecular bonds of the Van der Baals type, which causes the low energy of their crystal lattice. In this regard, the electronic structure of individual molecules during the formation of a crystal does not change significantly, and the properties of the crystals almost completely preserve the individual features of the molecules in combination with new properties caused by their collective interaction. This determines the main features of optical and electrophysical properties of OS, their energy structure of neutral and ionized states. In this article, it is experimentally confirmed that the planar structure of atoms of molecular crystals, in particular, linear acenes, and therefore the number of π-electrons responsible for exciton absorption in the visible region of the spectrum determines the position of the edge of their own optical absorption. It was also confirmed that the long-wavelength shift of the optical absorption edge of thin films of phthalocyanines is observed when atoms of heavy elements, for example, lead, are introduced into the molecule. When atoms of lighter elements are introduced into the phthalocyanine molecule, their planarity is not disturbed, and the long-wavelength shift of the edge is much smaller. An explanation of such changes is presented based on the interaction of foreign atoms with the π-electron system of phthalocyanine rings of neighboring molecules. The significant influence of the technological parameters of production, in particular the temperature of the substrate during thermal sputtering, on the crystal structure and optical properties of thin films of linear polyacenes and metallophthalocyanines has been demonstrated and substantiated. The possibility of controlling and presetting the necessary properties of thin-film condensates of molecular crystals is shown = В останні десятиліття привернули до себе особливу увагу тонкі плівки органічних напівпровідників (ОН), або, як їх ще називають, органічних молекулярних кристалів у зв’язку із цілим рядом пропозицій щодо їх використання у функціональних вузлах сучасної електроніки, а отже в сучасному технологічному обладнанні. При цьому дуже важливими є оптичні, електрофізичні та фотоелектричні властивості ОН, які визначаються як будовою органічних молекул, тобто вихідним матеріалом, так і кристалічною структурою конденсатів, тобто технологічними умовами отримання плівок. У зв’язку із цим, в даній статті викладені результати досліджень деяких властивостей OH і технології отримання тонких плівок на їхній основі. OH характеризуються слабкими міжмолекулярними зв’язками типу Ван-дер-Bаальсівських, що зумовлює низьку енергію їх кристалічної ґратки. У зв’язку із цим електронна структура окремих молекул при утворенні кристалу суттєво не змінюється, і у властивостях кристалів майже повністю зберігаються індивідуальні особливості молекул у поєднанні з новими властивостями, зумовленими їх колективною взаємодією. Це визначає головні особливості оптичних і електрофізичних властивостей ОН, їхню енергетичну структуру нейтральних та іонізованих станів. В даній статті експериментально підтверджено, що планарна структура атомів молекулярних кристалів, зокрема, лінійних аценів, а отже і кількість π-електронів, які відповідають за екситонне поглинання у видимій області спектру визначає положення краю їх власного оптичного поглинання. Підтверджено також, що довгохвильовий зсув краю оптичного поглинання тонких плівок фталоціанінів спостерігається при введенні в молекулу атомів важких елементів, наприклад, свинцю. При введенні в молекулу фталоціаніну атомів легших елементів їхня планарність не порушується, і довгохвильовий зсув краю значно менший. Представлено пояснення таких змін на основі взаємодії чужорідних атомів з π-електронною системою фталоціанінових кілець сусідніх молекул. Продемонстровано і обґрунтовано суттєвий вплив технологічних параметрів отримання, зокрема, температури підкладки при термічному напиленні на кристалічну структуру і оптичні властивості тонких плівок лінійних поліаценів та металофталоціанінів. Показано можливість керувати і наперед задавати необхідні властивості тонкоплівкових конденсатів молекулярних кристалів.
Keywords: органічні напівпровідники; молекулярні кристали; тонкі плівки; organic semiconductors; molecular crystals; thin films; напівпровідники